Stable and Reusable Palladium Nanoparticles‐Catalyzed Conjugate Addition of Aryl Iodides to Enones: Route to Reductive Heck Products. Issue 21 (7th November 2017) - Parveen, Naziya; Saha, Rajib; Sekar, Govindasamy
Abstract: An efficient, binaphthyl‐backbone‐stabilized palladium nanoparticles (Pd‐BNP) catalyst for the 1, 4‐addition of aryl halides to enones has been developed. The scope of the reaction has been studied with various substituted and sterically hindered aryl halides and enones to afford the conjugate addition products in good to excellent yields. The catalyst has been recovered and reused up to five times without any appreciable change in particle size or reactivity. Abstract :